Design and testing of a novel exhaust air energy recovery wind turbine generator / Ahmad Fazlizan Abdullah - Ahmad Fazlizan, Abdullah (2016)

(untitled)
An innovative system to recover part of the energy from man-made wind resources (exhaust air systems) is introduced. A vertical axis wind turbine (VAWT) in cross-wind orientation, with diffuser-plates is mounted above a cooling tower’s exhaust fan to harness the wind energy for producing electricity. The diffuser-plates are designed as a power-augmentation device to improve the performance of the VAWT as well as the cooling tower airflow performance. The performance of the VAWT and its effects on the cooling tower were investigated by experiment. A small scale of cooling tower is fabricated to mimic the actual counter-flow induced draft cooling tower. The supporting structure to hold the VAWT and dynamometer where turbine the position can be moved vertically and horizontally to study the performance in various configurations. The wind from the discharge outlet is generated by fan which is not in uniform profile. From the experiment, it is determined that the best horizontal position of the VAWT with a diameter of 300 mm at the outlet of the cooling tower with the outlet diameter of 730 mm is when the center of the turbine is at a distance of 250 mm to the center of the outlet. The distance is about 2/3 of the outlet radius. However, the vertical distance of the VAWT to the outlet is different depending on the fan speed. Based on the evaluation on the VAWT performance as well as the cooling tower performance, the best configuration of the system at fan speed of 708 rpm is when the VAWT is at horizontal position of 250 mm and vertical position of 350 mm. At this configuration, the cooling tower’s flow rate improved by 9.55%, the fan motor power consumption reduced by 2.07% while the turbine generating energy. For the fan speed of 910 rpm, the best VAWT position at the outlet of the cooling tower is at horizontal position of 250 mm and vertical position of 400 mm with the air flow rate of the cooling tower and fan motor consumption showed a 9.09% increase and 3.92% decrease respectively. The double multiple stream tube analysis produced similar pattern of graphs to the experimental result which indicates an v agreement between these two analyses. Theoretical analysis explains the wind turbine behavior in the not uniform wind stream as acquired from the experiment. For the selected wind turbine, it is the best to match the highest wind velocity region to the wind turbine at the range of 45° to 115° azimuth angle. This is as shown by the wind turbine at the positions of X = 250 mm and -250 mm. At this range of azimuth angle, the turbine produces higher instantaneous torque and better angle of attack compared to the other azimuth angle. The dual rotor exhaust air energy recovery turbine generator experiments found that the system produced the best performance at the VAWT vertical distance of 300 mm to the outlet plane. The integration of diffuser-plates further improved the VAWT performance with 20% and 27% for the fan speed of 708 rpm and 910 rpm respectively. At 910 rpm, with the diffuser-plates, the cooling tower air flow rate improved by 10.05% and the fan consumption decreased by 2.68% compared to the bare cooling tower. It also improved the energy recovery by 27.03% compare to the VAWT without diffuser-plates. For the actual size of cooling tower, it is estimated that 13% of the energy from the common cooling tower with the outlet size of 2.4 m and rated motor consumption of 7.5 kW is recovered. For the cooling tower that operates for 20 hours per day, every day throughout the year, a sum of 7,300 kWh/year is expected to be recovered. The payback period for the system of this size is 7 years while the net present value of the system at the end of the life cycle of the analysis is RM 25,437. The cumulative recovered energy value at the end of the life cycle of the system is RM 179,786. This system is retrofit-able to the existing cooling towers and has very high market potential due to abundant cooling towers and other unnatural exhaust air resources globally. In addition, the energy output is predictable and consistent, allowing simpler design of the downstream system.